THE EFFECT OF USING FLASH CARD MEDIA ON ENGLISH VOCABULARY MASTERY OF GRADE 8 STUDENTS OF AL-IKHLAS ISLAMIC JUNIOR HIGH SCHOOL JATIMAKMUR BEKASI - Ulfa Nur Azizah (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2025)
This study aims to evaluate the effectiveness of using flash card media in improving English vocabulary mastery among 8th grade students at SMP Islam Al-Ikhlas, Bekasi. This study used a quasi-experimental approach with a Nonequivalent Control Group design. A total of 50 students were divided into two groups, namely the experimental group and the control group. Data were collected through pretest and posttest, then analyzed using SPSS software to determine significant differences in learning outcomes between the two groups. The results showed that the average posttest score of the experimental group increased from 67.44 to 79.48, while the control group showed an increase from 69.36 to 75.72. Statistical analysis with the t-test showed that the use of flash card media had a significant impact on students' vocabulary mastery, with a sig. (2-tailed) value of 0.165, which indicated a significant difference in vocabulary mastery between students who used flash card media and those who did not. The conclusion of the study recommends the use of flash cards as an interactive and effective method in learning foreign language vocabulary, as well as encouraging the development of other visual learning media to improve student learning outcomes.